Analisis Penerapan Sistem Manajemen Keselamatan Sisi Udara di Bandar Udara Tunggul Wulung Cilacap - Rachman Wibowo, Arief; Kifni Yudianto (MES Bogor, 2025)
The increasing aviation industry, the implementation of a safety management system is expected to be able to overcome the occurrence of aviation traffic accidents and reduce the number of aviation accidents. Aircraft accidents continue to overshadow the rapid development of the aviation industry in Indonesia. There were 19 accidents and 26 major incidents in 2016, according to data from the National Transportation Safety Committee (KNKT). There were eleven aircraft accidents and seventeen major incidents in 2015, therefore, this shows an increase. Reported from KOMPAS TV explains